PATIENT WITH LATE DIAGNOSIS OF TYPE 2 DIABETES MELLITUS AND DIABETIC NEUROPATHY: CASE REPORT - Pereira, Pabloena da Silva; Falcão, Juliana Martins; de Araújo, Maria Luiza Costa; Tourinho , João Carlos Martins; Pereira, Bibiana Priscila Nunes; dos Santos, Yzabel Rielley Fonseca (Seven Editora, 2025)
The present study aims to describe, through a clinical case report and the systematic construction of the Nursing Process, the care provided to a patient diagnosed with type 2 Diabetes Mellitus (DM2) and Systemic Arterial Hypertension (SAH), both associated with the complication of Peripheral Diabetic Neuropathy. The methodological approach is based on the elaboration of four Nursing Processes based on the classifications of NANDA, NIC and NOC, characterizing the study as explanatory and correlational. The clinical case refers to the patient identified by the initials S.D.C., and data collection was carried out at his home, located in the city of Manaus, state of Amazonas. In addition, bibliographic searches were carried out in the electronic databases PubMed, LILACS and SciELO, with the objective of theoretically substantiating the discussion of clinical findings and nursing planning. This case report reinforces the significant risks associated with inadequate control of DM2 and SAH, which can result in chronic complications, such as peripheral neuropathy. Thus, the importance of continuous and effective monitoring by a multiprofessional team is evidenced, as well as the adoption of strategies that favor treatment adherence. Such actions are essential to prevent or minimize complications that compromise the quality of life and functional autonomy of patients affected by these chronic conditions. DOI: https://doi.org/10.56238/sevened2025.018-031